2017
DOI: 10.1007/s41060-017-0051-4
|View full text |Cite
|
Sign up to set email alerts
|

Improving the prediction of wind power ramps using texture extraction techniques applied to atmospheric pressure fields

Abstract: Much recent research in wind power forecasting has been focused on predicting large, sudden changes in wind power output, called wind ramps. State-of-the-art wind ramp prediction methods estimate future wind ramps from forecast power time series. We suggest that, by analyzing the weather associated with wind ramps, their forecasting can be improved. In particular, we propose a new method for wind ramp forecasting based on the analysis of forecast atmospheric pressure fields. Feature vectors relating to the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…where Mag(k) is the ramp magnitude when the k-th cluster of the wind speed forecast profile is extracted in the time series framework, and Mag(t 0 ) is the ramp magnitude forecast if a ramp occurs at t 0 . Figure 12 gives an example of the proposed day-head wind power ramp forecasting scheme with the ramp magnitude estimation, where the top orange line is the magnitude forecast calculated based on (7), and red error bar represents the measured magnitude of an actual ramp event with an acceptable error range of ±20%, which is one of ramp forecast requirements of the evaluation criteria suggested in [31].…”
Section: Forecasting Algorithm Implementationmentioning
confidence: 99%
See 2 more Smart Citations
“…where Mag(k) is the ramp magnitude when the k-th cluster of the wind speed forecast profile is extracted in the time series framework, and Mag(t 0 ) is the ramp magnitude forecast if a ramp occurs at t 0 . Figure 12 gives an example of the proposed day-head wind power ramp forecasting scheme with the ramp magnitude estimation, where the top orange line is the magnitude forecast calculated based on (7), and red error bar represents the measured magnitude of an actual ramp event with an acceptable error range of ±20%, which is one of ramp forecast requirements of the evaluation criteria suggested in [31].…”
Section: Forecasting Algorithm Implementationmentioning
confidence: 99%
“…Li et al. [7] and [8] used additional meteorological variables, atmospheric pressure fields and Foehn wind, respectively, to improve the prediction of wind power ramps. However, they could not be used as a generic solution to wind power ramp forecast due to the high requirement for meteorological expertise and the limitation on specific geographical environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In ML, the performance on an unseen data is highly dependent on the input feature set, and the dimensionality of input features during training phase governs the computational time and the generalization performance. In Reference 23, the prediction performance of a feature extraction technique based on Gabor filtering and considering atmospheric pressure fields, is found to be better than the state‐of‐the‐art neural network method. Figure 1 illustrates a graphic for ML performance with respect to the number of features.…”
Section: Introductionmentioning
confidence: 99%
“…Three wind speed datasets from Spain are considered to evaluate the accuracy of hybrid method for classifying wind power ramp events. In [22], the authors have presented a feature extraction method based on Gabor filtering where the atmospheric pressure fields are taken into consideration. Results are compared with state-of-the-art neural network method and it is found that Gabor method with its change in power as its output gives a better prediction performance.…”
Section: Introductionmentioning
confidence: 99%